Post-Crisis Leadership : resilience, renewal, and reinvention in the aftermath of disruption - Gigliotti, Ralph A. (New Brunswick, New Jersey: Rutgers University Press, 2025)
"Given the many pressures facing leaders across higher education, the work of crisis leadership remains an imperative for leaders at all levels. Attention tends to center on strategies for engaging in leadership both prior to and during crisis, often leaving the post-crisis period as an afterthought. This book introduces a research-informed framework for this critical, and often neglected, phase of crisis leadership. With an underlying commitment to values-based, principle-oriented, and people-centered practices, this framework consists of five leadership practices that are recognized as especially critical in the aftermath of crisis: (a) encourage learning, (b) inspire growth, (c) stimulate meaning making, (d) pursue reinvention, and (e) advance renewal. Communication serves a critical role in each of the various dimensions of post-crisis leadership, and it is a communication orientation that can help to inform the paradoxes, processes, and patterns that arise during these periods of immense tension and, at times, transcendence"
Introduction : contemporary crisis conditions and theoretical underpinnings for post-crisis leadership -- Encourage learning -- Cultivate resilience -- Stimulate meaning making -- Pursue reinvention -- Advance renewal -- Conclusion.
Keywords: Education, Higher -- Administration. -- United States; Crisis Management -- United States; Universities and Colleges -- Administration. -- United States; $a Educational Leadership -- United States; Communication in Higher Education -- United States